Libraries and the Sustenance of Indigenous Knowledge in the Creative Arts - Yankah, Kwesi (Ghana Library Journal, 2005)
I begin this presentation with a few assumptions about the concept of indigenous knowledge: that is knowledge or rather the intellectual property of an illiterate society, that relies largely on oral traditions to transmit and preserve their knowledge. If one decides to juxtapose this concept with the concept of the library as an institution, for the preservat ion of literary material, (books, journals, or materials preserved through writing) you realize immediately the apparent contradiction. To what extent are libraries relevant in the preservation of oral traditions, indigenous knowledge?